Demonstration of Borage Salinity Tolerance as affected by Si Application Through Biochemical and Physiological Responses, and Growth Attributes - Feghhenabi, Farideh (2023)
Borage (Borago officinalis L.) is an oilseed that is being increasingly grown in areas where salinity affects yield. Silicon (Si) supplementation is considered a promising method to improve plant growth in saline conditions, however, there is currently very little information on the effect of Si application on the physiochemical properties of borage under saline conditions. The study aimed to elucidate if the degree of borage resistance to salinity is changed by Si through the physiochemical properties. We conducted a pot experiment to explore photosynthetic pigments, chlorophyll fluorescence parameters, osmolyte content, oxidative stress, and antioxidant response as influenced by increasing salinity levels and Si applications (priming, foliar spray, and priming × foliar spray). Salinity-stressed plants had a noticeable decline in chlorophyll a (56.6%) and b (64.2%), carotenoid content (57.5%), chlorophyll fluorescence parameters (Fv/Fm (7.2%), ETR (23.2%), and ΦPSII (15.2%)), and growth characteristics. Salinity increased oxidative damage through excessive production of malondialdehyde and increased electrolyte leakage in leaves. The salinity-stressed plants also showed high antioxidant activities of catalase and superoxide dismutase and increased accumulation of glycine betaine and soluble sugars compared to non-stressed plants. Si treatments resulted in a significant reduction in oxidative damage and increased antioxidant activity reducing lipid peroxidation and electrolyte leakage in the salinity-stressed leaves. The priming × foliar spray was the most effective at enhancing borage salinity tolerance. We, therefore, assumed that the investigated physicochemical properties could clearly describe the physiological context of salinity tolerance in borage and that Si could be used as a mediator of salinity tolerance and positively affect growth characteristics.